O funcionamento da noção de “sujeito-corpo” no estatuto da pessoa com deficiência e nos textos sobre este documento - Marchesan, Andressa (2019)
This thesis inscribes itself within the French Discourse Analysis tradition developed by Michel Pêcheux and Eni Orlandi, as well as by other researchers in Brazil. In this study, we analyze the designations referring to disabled people, and how their bodies are defined. We question ourselves about the functioning of the “body-subject” notion in the Statute of the Disabled and texts about it. For this purpose, we selected the Statute and four texts about it as the archive. The first one is from Senator Paulo Paim‟s speech at the opening of the seminar about the Statute of the Disabled. The second one is a guide to the Statute, written by Congresswoman Mara Gabrilli. The third is a news story entitled “On the first anniversary of the Brazilian Inclusion Law, advances in education are visible”, Jornal do Senado, July 1st, 2016. The fourth is a text from the former president Dilma Rousseff, during the sanctioning ceremony of the Statute of the Disabled. Besides the analyzed objects, we also consulted dictionaries in order to constitute the process of meaning construction. Our analysis showed that the juxtaposition “body-subject”, which was constituted to bridge the existing gap between the terms, does not convey proximity in both the Statute and texts about it. Instead, it produces other meanings because disabled bodies are silenced or mentioned implicitly. The subject is neither mentioned nor silenced - that is, the individual who is on the margin of society appears. Our magnifying glass does not see normality nor abnormality; on the contrary, it sees a subject who is different from the other, a different body, a different norm, each “body-subject” with their singularities...their already-said...their silences...